Financial freedom and bank efficiency: Evidence from the European Union - Chortareas, Georgios E.; Girardone, Claudia; Ventouri, Alexia (Journal of Banking & Finance, 2013)
This paper investigates the dynamics between the financial freedom counterparts of the economic freedom index drawn from the Heritage Foundation database and bank efficiency levels. We rely on a large sample of commercial banks operating in the 27 European Union member states over the 2000s. After estimating bank-specific efficiency scores using Data Envelopment Analysis (DEA), we develop a truncated regression model combined with bootstrapped confidence intervals to test our main hypotheses. Results suggest that the higher the degree of an economy’s financial freedom, the higher the benefits for banks in terms of cost advantages and overall efficiency. Our results also show that the effects of financial freedom on bank efficiency tend to be more pronounced in countries with freer political systems in which governments formulate and implement sound policies and higher quality governance.